Intrarater reliability of different methods of heart rate variability threshold analysis and postexercise parasympathetic reactivation in young women - Bruno Guilhen Ribeiro; Raiane Maiara dos Santos Pereira; Rafaello Pinheiro Mazzoccante; Leonardo Pereira; Adriano Drummond; Lúcia Kobayashi; Guilherme Eckhardt Molina; Carlos Janssen Gomes da Cruz (Universidade Estadual Paulista (UNESP), 2021)
Abstract Objective: To evaluate the reliability of HRVT and postexercise parasympathetic reactivation analysis after a submaximal exercise test in young women. Methods: Twenty-four young women [21.1 (20.1, 24.7) years; 21.4 (20.1, 23.1) kg/m2] underwent three incremental exercise tests on a treadmill on occasions separated by 48 h. R-R intervals were continuously recorded during the incremental tests and throughout 5 min of post-exercise active recovery for HRVT and parasympathetic reactivation analysis, respectively. HRVT was identified using two methods: a) the intensity where no significant reduction of SD1 HRV index was identified by visual inspection of the graphic (HRVTvisual), b) the first stage to present SD1 value < 3ms (HRVT3ms). Postexercise parasympathetic reactivation was assessed at each minute during five minutes of recovery using SD1 and r-MSSD indexes. Absolute and relative reliability were assessed using the coefficient of variation (CV) and the intraclass correlation coefficient (ICC), respectively. Results: Good (ICC = 0.81, CV = 17.3) and excellent (ICC = 0.90, CV = 4.6) reliability were observed for HRVT3ms and HRVTvisual, respectively. On the postexercise period, good reliability was observed for both SD1 (ICC = 0.82-89, CV = 22.1-28.9) and r-MSSD (ICC = 0.82-89, CV = 21.1-28.6), with a high correlation between indexes in all-time points of analysis (r = 0.96-0.99). Conclusions: HRVT may be reproducibly assessed in women, mainly when HRVTvisual is used for analysis. In addition, SD1 and r-MSSD provide reliable and redundant measures of postexercise parasympathetic reactivation.